2022
DOI: 10.1093/hmg/ddac135
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar contribution to threat probability in a SCA6 mouse model

Abstract: Fear and anxiety have proven to be essential during the evolutionary process. However, the mechanisms involved in recognizing and categorizing threat probability (i.e. low to high) to elicit the appropriate defensive behavior has yet to be determined. In this study we investigated the cerebellar contribution in evoking appropriate defensive escape behavior using a purely cerebellar, neurodegenerative mouse model for spinocerebellar ataxia type 6 (SCA6) which is caused by an expanded CAG repeat in exon 47 of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…Studies on spinocerebellar ataxia (SCA) rodent models also support a cerebellar role in anxiety behavior. SCA models are generally characterized by abnormal expansion of CAG repeats in genes that lead to an ataxic pathology due to neurodegeneration in the cerebellum, often in Purkinje cells (Boy et al, 2009(Boy et al, , 2010Kelp et al, 2013;Asher et al, 2021;Bohne et al, 2022). Anxiety behavior is one of the most studied behaviors amongst the various non-sensorimotor impairments also observed in SCA models, beyond their characteristic ataxic phenotype.…”
Section: Spinocerebellar Ataxia Rodent Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on spinocerebellar ataxia (SCA) rodent models also support a cerebellar role in anxiety behavior. SCA models are generally characterized by abnormal expansion of CAG repeats in genes that lead to an ataxic pathology due to neurodegeneration in the cerebellum, often in Purkinje cells (Boy et al, 2009(Boy et al, , 2010Kelp et al, 2013;Asher et al, 2021;Bohne et al, 2022). Anxiety behavior is one of the most studied behaviors amongst the various non-sensorimotor impairments also observed in SCA models, beyond their characteristic ataxic phenotype.…”
Section: Spinocerebellar Ataxia Rodent Modelsmentioning
confidence: 99%
“…Interestingly, in certain SCA models, both abnormalities in anxiety behavior could be observed 2021) demonstrated that SCA 1 knock-in mice display anxiogenic traits, whereas Purkinje cell-specific SCA 1 knock-in mice exhibit anxiolytic behavior. Additionally, Bohne et al (2022) showed that in their SCA 6 mouse model, reduced anxiety was observed in low-threat conditions, but these mice displayed enhanced anxious defensive behaviors in contexts with higher aversiveness. This suggests a possible miscalculation of threat probability due to cerebellar pathology.…”
Section: Spinocerebellar Ataxia Rodent Modelsmentioning
confidence: 99%
“…Lesions within the rat cerebellar vermis decreased innate fear, seen by an increase in approach behavior in the cat test and enhancement of motor activity in the open field test in comparison with the controls (Supple et al, 1987). Additionally, in a recent study, a spinocerebellar ataxia mouse model with alterations exclusively to PCs was accessed in innate fear-and anxietyrelated assays, such as the open field, elevated plus maze, and light/dark place preference assay (Bohne et al, 2022). Affected mice spent more time in the center and intermediate area of the open field, in the open arms of the elevated plus maze, and in the light zone of the light/dark box, thereby suggesting an anxiolytic-like phenotype of the spinocerebellar ataxia mouse model.…”
Section: Cerebellar Contribution To Innate Behavioral Threat Responsesmentioning
confidence: 99%
“…However, when the threat level was escalated, i.e., when mice were exposed to aversive sounds, bright light conditions, or a looming stimulus, mice exhibited enhanced anxiety-like behavioral patterns. These aberrant defensive behavioral responses in mice with spinocerebellar ataxia (Bohne et al, 2022) suggest that cerebellar degeneration affects innate defensive responses in a complex manner, possibly via impacting correct assessment of threat levels. Curiously, patients with spinocerebellar ataxia showed reduced predictive and reactive motor timing tasks (Broersen et al, 2016), thereby confirming cerebellar involvement in timing function and generation of prediction errors and suggesting a putative similar mechanism for regulating innate defensive responses.…”
Section: Cerebellar Contribution To Innate Behavioral Threat Responsesmentioning
confidence: 99%
“…CT-long Q27 mice which express elongated C-terminal fragments of the P/Q-type channel develop typical SCA6 symptoms including ataxia and PC degeneration, highlighting the importance of the C-terminus in SCA6 pathology (Mark et al, 2015). Recently, these mice were shown to exhibit a decrease in innate fear and defense behavior (Bohne et al, 2022). Another rodent model that closely mimics SCA6 both genetically and phenotypically are SCA6 84Q mice (Watase et al, 2008).…”
Section: Introductionmentioning
confidence: 99%